2010
DOI: 10.1142/s0217979210064320
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Principles of Some Trends in Properties of Metallic Hydrides

Abstract: Due to their extensive present, important and versatile potential applications, metal hydrides (MH) are among the most investigated solid-state systems. Theoretical, numerical and experimental studies have provided a considerable knowledge about their structure and properties, but in spite of that, the basic electronic principles of various interactions present in MH have not yet been completely resolved. Even in the simplest MH, i.e. alkali hydrides (Alk-H), some trends in physical properties, . Int. J. Mod. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A very recent computational study of some metal hydrides reported a saddle point in ρ ( r ) between two hydrogen atoms in 4 , although this was not analyzed further 11. Moreover, a recent experimental study of 4 assigned a significant amount of charge (0.25 e Å −3 ) to the region between the bridging hydrogen atoms,12 in pleasing agreement with our computational results.…”
Section: Aim Charges (Q) and Salient Topological Parameters For The Tsupporting
confidence: 89%
See 1 more Smart Citation
“…A very recent computational study of some metal hydrides reported a saddle point in ρ ( r ) between two hydrogen atoms in 4 , although this was not analyzed further 11. Moreover, a recent experimental study of 4 assigned a significant amount of charge (0.25 e Å −3 ) to the region between the bridging hydrogen atoms,12 in pleasing agreement with our computational results.…”
Section: Aim Charges (Q) and Salient Topological Parameters For The Tsupporting
confidence: 89%
“…We turn now to consideration of two other light binary metal hydrides, LiH ( 5 ) and NaH ( 6 ), the calculated electron densities of which have been reported before,11 although the values cited were incomplete. These two alkali metal systems adopt the rock salt structure, with hydride ions occupying all octahedral holes in an fcc array of metal ions, but the smaller cation in 5 allows a close H⋅⋅⋅H approach of 2.85 Å (cf.…”
Section: Aim Charges (Q) and Salient Topological Parameters For The Tmentioning
confidence: 99%
“…They are also systems of considerable theoretical interest [15][16][17][18][19][20][21][22][23][24][25] convenient for investigation of fundamental interactions that are expected to be important in new complex materials [26][27][28][29][30][31][32]. Although significant experimental and theoretical work has been devoted to the study of metal hydrides, some of their fundamental features, such as details of valence and conduction bands and energy gap structures, the charge transfer and the charge distribution, the origin and the importance of various contributions to the bonding between metal and hydrogen (M-H) and hydrogen and hydrogen (H-H), are not yet fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…A complete elaboration of these topics from the first principles is indispensable for understanding of H-behavior in metallic systems in general. Moreover, extensive data about metal hydrides have been obtained and explained using various, and sometimes contradictory, concepts [15][16][17][18][20][21][22][23][24][25][26][33][34][35][36][37][38][39]. However, a coherent approach valid for all metal hydrides is still missing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation